Etiology and control of Gypsophila paniculata L. stem base rot in the Caraz Valley, Ancash - Aguilar-Anccota, R. (2020)
Gypsophila is an ornamental plant whose flowers are economically important, which is cultivated in the Callejón de Huaylas valley-Ancash. Recently, cultivated Gypsophila fields have shown diseased plants characterized by stem base rot, which has been followed by a reduction in vigor and the collapse and death of plants. Therefore, the objectives of this research were to describe the symptomatology of the disease, identify the causative agent of the disease, and prove how effective fungicides and biological control agents (BCA) are in controlling the disease using in vitro and field experiments. To isolate the pathogen, symptomatic plant tissue samples were washed, cut into small pieces, disinfected in 1% sodium hypochlorite solution for 1 min, rinsed twice with sterilized water, and air-dried on paper towels. The samples were seeded on Petri dishes containing potato dextrose agar media and incubated at 25 °C. A pathogenicity test was conducted in healthy Gypsophila seedlings, which were grown in a sterilized substrate, using mechanical inoculation on the stem base and agar disks colonized by the pathogen-mycelium. Then the pathogen was reisolated from symptomatic inoculated Gypsophila seedlings. The “poisoned medium” technique was used to conduct the in vitro fungicide test, while the “dual method” was used to conduct the bio controller’s test. The results of the pathogenicity test and in vitro and field experiments showed that Rhizoctonia solani is the causative agent of the stem base Gypsophila disease, and at both assayed doses, the fungicides Rovral, Benopoint, Parachupadera, Vitavax, and Homai completely inhibited the mycelial growth of R. solani. Moreover, the BCAs Trichoderma harzianum and T. viride showed higher in vitro growth rates than R. solani and completely colonized the pathogen-mycelium. Under field conditions, the incidence of the disease in field plots treated with T. harzianum was 12.5% lower than in the control treatment, which showed 51.28% incidence of the disease. In addition, Gypsophila plants harvested from plots treated with T. harzianum exhibited higher numbers of flower stalks per plant and a higher fresh weight compared to the control treatment.